2012
DOI: 10.1001/archopthalmol.2011.1846
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomographic Assessment of Severity of Cystoid Macular Edema in Retinopathy of Prematurity

Abstract: Objective To investigate whether the severity of cystoid macular edema (CME) in neonates who were 31 to 36 weeks’ postmenstrual age, as viewed by spectral-domain optical coherence tomography (SD-OCT) imaging, predicts the severity of retinopathy of prematurity (ROP) or is related to systemic health. Design Of 62 prematurely born neonates in a prospective institutional review board–approved study, 42 met the following inclusion criteria: at least 1 SD-OCT imaging session prior to 37 weeks’ postmenstrual age a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
118
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 111 publications
(133 citation statements)
references
References 40 publications
8
118
2
5
Order By: Relevance
“…The highest quality foveal scan of 1 randomly chosen eye was selected from each available imaging session by criteria including good contrast, ability to see inner retinal layers, and lack of tilt. Only 1 eye per infant was considered for analysis because Maldonado et al 11 demonstrated bilaterally of CME in all infants with both eyes imaged as well as a correlation coefficient of 0.989 for central foveal thickness (CFT) between study and fellow eyes. Each foveal scan was graded by 1 of the 2 graders qualitatively for the presence of CME and quantitatively for CFT, parafoveal thickness at 1000 µm distance inferiorly and superiorly from the foveal center for vertical scans or nasally and temporally from the foveal center for horizontal scans, and INL thickness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest quality foveal scan of 1 randomly chosen eye was selected from each available imaging session by criteria including good contrast, ability to see inner retinal layers, and lack of tilt. Only 1 eye per infant was considered for analysis because Maldonado et al 11 demonstrated bilaterally of CME in all infants with both eyes imaged as well as a correlation coefficient of 0.989 for central foveal thickness (CFT) between study and fellow eyes. Each foveal scan was graded by 1 of the 2 graders qualitatively for the presence of CME and quantitatively for CFT, parafoveal thickness at 1000 µm distance inferiorly and superiorly from the foveal center for vertical scans or nasally and temporally from the foveal center for horizontal scans, and INL thickness.…”
Section: Methodsmentioning
confidence: 99%
“…Resolution of CME is reported in some, but not all, cases, making it unclear whether this subclinical finding is a physiologic process during normal retinal development or a marker of underlying pathologic features. 11,12,14 …”
mentioning
confidence: 99%
“…We decided to evaluate two commercial platforms that are commonly used in human adult imaging, clinical research, and randomized clinical trials. [2][3][4] We chose a commercial hand-held portable platform approved for retinal imaging in pediatric human subjects 5,14,[20][21][22] and in basic animal research. [23][24][25] Furthermore, the largest ongoing randomized trial for age-related macular degeneration (AMD), the NEI-sponsored Age-Related Eye Disease Study 2, exclusively allows the Bioptigen SDOIS platform for its longitudinal, observational ancillary SDOCT study (AREDS2 Ancillary SDOCT Study).…”
Section: -10mentioning
confidence: 99%
“…SDOCT provides estimates of retinal layer thicknesses across the macula to aid in clinical diagnosis and treatment decisions for a variety of ocular diseases. [2][3][4][5][6] Interpretation of data has been complicated by the variety of platforms designed by commercial SDOCT instrument manufacturers, each with different proprietary software technologies. Previous studies have identified OCT-derived retinal thickness measurement variability due to differences in their segmentation algorithms, their reported axial resolutions in tissue, their scan density options, and their ability to correct for subject fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Os autores se propuseram a observar se a severidade do edema cistoide de mácula, encontrado em 50% dos 42 prematuros estudados, tinha algum valor preditivo para a necessidade de tratamento. Eles concluíram que o edema cistoide de mácula não estava diretamente relacionado com a gravidade preditiva para tratamento da retinopatia da prematuridade, mas a espessura foveal e parafoveal aumentada sim (24) . A relação encontrada neste estudo pode oferecer uma explicação para o que foi encontrado no grupo G1 do presente estudo, pois a espessura foveal foi significativamente maior nos prematuros deste grupo G1 em relação ao grupo G2.…”
Section: Discussionunclassified